Biological control: A major component of the pest management program for the invasive coconut scale insect, Aspidiotus rigidus Reyne, in the Philippines - Almarinez, Billy Joel M. (Animo Repository, 2020)
The coconut scale insect, Aspidiotus rigidus Reyne, caused a major pest outbreak in coconut plantations and stands in the Southern Tagalog region of Luzon Island in the Philippines between 2010 and 2015. To determine if parasitism by Comperiella calauanica Barrion, Almarinez and Amalin, a native encyrtid, could have been a factor in the eventual management of the outbreak by 2015, we estimated and assessed its parasitization levels on A. rigidus colonies on field-collected samples from selected points in three provinces in the Southern Tagalog Region across three sampling periods. We observed that C. calauanica consistently occurred only in areas where A. rigidus populations occurred, with high parasitization levels in the Southern Tagalog sites from 2014 to 2015. Results of correlation and regression of total scale count against parasitized scale count suggest putative host density-dependent parasitism by C. calauanica in the field. A marked decrease in the abundance of A. rigidus was recorded concurrently with visually observable recovery of coconut trees from the third quarter of 2014 up to the second quarter of 2016. Similar results of significant reduction in A. rigidus populations concurrent with high percent parasitization by mass-reared and released C. calauanica were found in the Zamboanga Peninsula from 2018 to 2020. Our findings and observations altogether suggest that host-specific parasitization by C. calauanica effected biological control, which may have contributed to the eventual management of the A. rigidus outbreak in the Southern Tagalog Region, and also in the Zamboanga Peninsula where similar recovery of coconut trees were observed within a year after inoculative releases of C. calauanica.